2017
DOI: 10.18632/oncotarget.18026
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum chaperone prolyl 4-hydroxylase, beta polypeptide (P4HB) promotes malignant phenotypes in glioma via MAPK signaling

Abstract: Endoplasmic reticulum (ER) chaperone Prolyl 4-hydroxylase, beta polypeptide (P4HB) has previously been identified as a novel target for chemoresistance in glioblastoma multiforme (GBM). Yet its functional roles in glioma carcinogenesis remain elusive. In clinical analysis using human glioma specimens and Gene Expression Omnibus (GEO) profiles, we found that aberrant expression of P4HB was correlated with high-grade malignancy and an angiogenic phenotype in glioma. Furthermore, P4HB upregulation conferred malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…These preliminary in vitro experimental results confirmed that P4HB may be associated with the development and progression of bladder cancer. Previous studies have demonstrated that PH4B can induce malignant tumor cell proliferation, invasion and metastasis by regulating hypoxia inducible factor-1α (HIF-1α) expression and the MAPK signaling pathway (42,43). In our present study, we found that P4HB expression was positively associated with the expression levels of ANAPC11, STRA13, and SLC397A and negatively associated with the expression levels of ZSWIM6, LYRM7, and WDR36 ( Figure 7A).…”
Section: Figure 9 |supporting
confidence: 69%
“…These preliminary in vitro experimental results confirmed that P4HB may be associated with the development and progression of bladder cancer. Previous studies have demonstrated that PH4B can induce malignant tumor cell proliferation, invasion and metastasis by regulating hypoxia inducible factor-1α (HIF-1α) expression and the MAPK signaling pathway (42,43). In our present study, we found that P4HB expression was positively associated with the expression levels of ANAPC11, STRA13, and SLC397A and negatively associated with the expression levels of ZSWIM6, LYRM7, and WDR36 ( Figure 7A).…”
Section: Figure 9 |supporting
confidence: 69%
“…24 P4HB plays a critical role in carcinogenesis in glioma, and overexpression of P4HB leads to proliferation, invasion, migration and angiogenesis in vivo and increases tumor growth through the mitogen-activated protein kinase (MAPK) signaling pathway in vitro. 25 Genetic and pharmacological inhibition of P4HB induces ERS, and early-stage ERS has protective effects on cells and promotes malignancy of tumor cells, making tumors resistant to apoptosis induced by ERS. 8 However, persistent ERS induces apoptosis to prevent tumor cells from proliferating.…”
Section: Discussionmentioning
confidence: 99%
“…P4HB, a beta subunit of Prolyl 4-hydroxylase, might help cancer cells survive from apoptosis induced by endoplasmic reticulum (ER) stress [30,31]. P4HB promoted proliferation, invasion, migration and angiogenesis in glioma through mitogen-activated protein kinase (MAPK) signaling pathway [32]. In gastric cancer, P4HB was proved to play an important role on regulating invasion and migration in the hypoxia-inducible factor 1a (HIF1a) network [33].…”
Section: Discussionmentioning
confidence: 99%